INTELLECTUAL HELP-SYSTEM AS THE TUTORIAL TO TECHNOLOGIES OF PROGRAMMING (Journal of Information Technologies in Education (ITE), 2010)
The object of consideration is help-system on technologies of programming.. Opportunities of using help-systems as computer means of training are considered in the article. Intellectual help-system on technology of programming, oriented to handling semantic nets, and options of its usage for training are described here.
Keywords: computer means of training; help-system; programming technologies